Comprehensive evaluation and selection of the potential complex medium for industrial glutamate decarboxylase (GAD) production by Escherichia coli - Yao, Wanying; Wu, Xiao; Zhu, Jun; Sun, Bo (International Journal of Agricultural and Biological Engineering, 2011)
<span style="line-height: 135%; font-family: